(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The most significant type of expressive is body language. Nonverbal communication. Face expression recognition (FER) systems have been developed to serve real-world applications rather than laboratory settings, owing to advances in hardware and sensor technologies. FER is a technique of communicating social information without the need of words. FER may be utilized in a number of settings, including healthcare, education, criminal investigation, and HMI (Human Robot Interface) (HRI). FER systems are being utilized in a variety of industries, including healthcare, robotics, education, and entertainment. In this article, the author discusses Face Expression Recognition and the steps involved in the FER system, such as face detection, extraction, and expression categorization. Everything, like any new technology, has advantages and drawbacks. When utilizing the AFEW dataset, the FER system also has a problem with accuracy, since the accuracy is only 50%. With the advancement of technology, this precision will increase in the future. As a result, the FER system has a promising future.